Taxonomic review of the genus Lista Walker, 1859 from China (Lepidoptera, Pyralidae, Epipaschiinae), with descriptions of five new species - Rong, Hua; Wang, Yiping; Qi, Mujie; Li, Houhun (Zootaxa, 2021)
The genus Lista Walker, 1859 from China is reviewed. Of the eighteen species treated, five species are described as new: L. furcellata Li & Rong, sp. nov., L. serrata Li & Rong, sp. nov., L. strumiformis Li & Rong, sp. nov., L. yunnanensis Li & Rong, sp. nov. and L. zhengi Li & Rong, sp. nov. Photographs of adults and genitalia of the new speices are provided. A key based on male genitalia to all Chinese species is provided.